Film theory: an introduction through the senses - St-Georges.D, Charles (Imagofagia, 2021)
Sobre Elsaesser, Thomas y Malte Hagener. Film theory: an introduction through the senses. New York, Routledge, 2010, 222 pp., ISBN 9780415801003. Palabras clave: critica, Elsaesser Thomas, Malte Hagener, Film theory: an introduction through the senses